Herlyn-Werner-Wunderlich syndrome with double hematocolpos in one side hemivagina - You Jin Kim; Jung Bo Yang; Ye Won Jung; Soo Youn Song; Geon Woo Lee; Heon Jong Yoo (IMR Press, 2022)
Background: Herlyn-Werner-Wunderlich syndrome (HWWS) is an extremely rare Mullerian anomaly consisting of uterus didelphys with obstructed hemivagina and ipsilateral renal agenesis. Although few HWWS cases had been reported in the gynecological literature, most of the reported cases were combined with single hematocolpos. Case: We report here on a case of HWWS with double hematocolpos on one side of a hemivagina combined with ipsilateral renal agenesis. This is the first report of HWWS with double hematocolpos on one side of a hemivagina that was successfully treated with the resection of the vaginal septum. Conclusion: It is important to understand the pathogenesis and clinical features of these anomalies for diagnosis.